Bigger, stronger, faster, fitter: the differences in physical qualities of school and academy rugby union players. Issue 21 (2nd November 2018) - Jones, Ben; Weaving, Dan; Tee, Jason; Darrall-Jones, Joshua; Weakley, Jonathon; Phibbs, Padraic; Read, Dale; Roe, Gregory; Hendricks, Sharief; Till, Kevin
ABSTRACT: Limited research has compared the physical qualities of adolescent rugby union (RU) players across differing playing standards. This study therefore compared the physical qualities of academy and school Under-18 RU players. One-hundred and eighty-four (professional regional academy,   n  = 55 school,   n  = 129) male RU players underwent a physical testing battery to quantify height, body mass, strength (bench press and pull-up), speed (10, 20 and 40 m), 10 m momentum (calculated; 10 m velocity * body mass) and a proxy measure of aerobic fitness (Yo-Yo Intermittent Recovery Test Level 1; IRTL1). The practical significance of differences between playing levels were assessed using magnitude-based inferences. Academy players were taller ( very likely small ), heavier ( likely moderate ) and stronger (bench press  possibly large ; pull-up plus body mass  likely small ) than school players. Academy players were faster than school players over 20 and 40 m ( possibly  and  likely small ), although differences in 10 m speed were not apparent ( possibly trivial ). Academy players displayed greater 10 m momentum ( likely moderate ) and greater IRTL1 performance ( likely small ) than school players. These findings suggest that body size, strength, running momentum, 40 m speed and aerobic fitness contribute to a higher playing standard in adolescent rugby union.